Nanodispersions. - Tadros, Tharwat F. (De Gruyter, 2016)
Our book provides an introduction that covers nanodispersions. Most often used in the Pharmaceutical, Food and Cosmetics industry, liposomes are used to carry drugs, peptides, proteins, vitamins, and other actives to specific target destinations (organs).